2016
DOI: 10.1093/carcin/bgw077
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations in the Hippo signaling pathway and breast cancer risk in African American women in the AMBER Consortium

Abstract: The Hippo signaling pathway regulates cellular proliferation and survival, thus exerting profound effects on normal cell fate and tumorigenesis. Dysfunction of the Hippo pathway components has been linked with breast cancer stem cell regulation, as well as breast tumor progression and metastasis. TAZ, a key component of the Hippo pathway, is highly expressed in triple negative breast cancer; however, the associations of genetic variations in this important pathway with breast cancer risk remain largely unexplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 56 publications
0
25
1
Order By: Relevance
“…We were not able to compare our association findings in WWC1 and LATS2 with the previous study in African Americans because these two genes were not included in their custom genotyping assay design . In that study, CDH1 was found to be nominally associated with ER− breast cancer risk, and approached the borderline of significance for association with ER+ breast cancer risk, while we obtained a marginal significance with ER+ breast cancer risk.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…We were not able to compare our association findings in WWC1 and LATS2 with the previous study in African Americans because these two genes were not included in their custom genotyping assay design . In that study, CDH1 was found to be nominally associated with ER− breast cancer risk, and approached the borderline of significance for association with ER+ breast cancer risk, while we obtained a marginal significance with ER+ breast cancer risk.…”
Section: Discussioncontrasting
confidence: 68%
“…A few studies have examined the risk of breast cancer associated with genetic variations in the Hippo pathway . Single nucleotide polymorphisms (SNPs) in YAP1 and STK4 have been reported to be associated with breast cancer risk in Chinese and European populations, respectively .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…3, 9 out of 17 modules are significantly enriched in 26 KEGG pathways. Several enriched KEGG pathways are associated with breast cancer, such as Cell cycle [50], TGF-beta signaling pathway [51], Pathways in cancer, Hippo signaling pathway [52], Ras signalling pathway [53], ErbB signaling pathway [54], Chemokine signalling pathway [55], and Calcium signalling pathway [56]. Specifically, three modules (M2, M3, and M4) are significantly involved in the KEGG pathway: Breast cancer, suggesting that the three BRCA-related miRSCoPPI modules are closely associated with breast cancer.
Fig.
…”
Section: Resultsmentioning
confidence: 99%